Barriers to innovation in the housing sector: Economic justifiability of offsite construction for housebuilders. (15th July 2022) - Zolghadr, Ali; Gharaie, Ehsan; Naderpajouh, Nader
Abstract: The uptake of offsite construction in the housing sector is low, despite extensive discussions on its benefits. Offsite construction methods significantly disrupt the products and processes of the housing sector. In this context, the interactions of autonomous actors in a loosely coupled system within and beyond the industry determines desirability of offsite construction methods for different actors and consequently the uptake of the methods on sector level. As a result, there is a need to systematically synthesise the mechanisms that shape the desirability of offsite construction for industry practitioners. To fill this gap, a qualitative system dynamics model is developed in this research to study the feedback mechanisms that encourage/discourage application of offsite construction methods with a focus on economic justifiability of these methods for housebuilders. The model is developed via a grounded theory-based approach through a synthesis of the literature. A series of semi-structured interviews with industry experts are then carried out to verify and contextualise the model. The results indicate that a long-term holistic perspective accounting for the interactions of different actors can redefine economic justifiability and consequently improve desirability of offsite construction methods for builders, which will then feed back into the system to sustain the long-term benefits of all involved actors. The model is used to propose uptake strategies based on strengthening the feedback structures that reinforce economic justifiability of offsite construction methods and weakening those that decrease economic justifiability. Highlights: A qualitative system dynamics model is developed to study economic justifiability of offsite construction for housebuilders. A grounded theory-based methodology is used to develop the model using textual data from previously published literature. The model is verified and contextualised using semi-structured interviews with industry experts. The feedback mechanisms that shape economic justifiability of offsite construction for housebuilders are discussed. Strategies are proposed to increase the uptake of offsite construction by increasing economic justifiability for builders.